Arterial hypertension in patients with coronary artery disease treated with surgical myocardial revascularization - Vavlukis, M; Borozanov, V; Georgievska-Ismail Lj; Bosevski, M; Taneva, B; Kostova, N; Peovska, I (AEP Press, 2007)
Objectives: To evaluate the incidence and prognostic power of arterial hypertension in patients with coronary artery disease treated with surgical myocardial revascularisation, before and after the operation. Background: Arterial hypertension is one of the leading modifiable risk factors in CAD patients who underwent CABG surgery with the major impact on clinical outcome in these patients. Methods: 749 patients with mean age of 55 +/- 8 years, (639 male/119 female) were analyzed for their preoperative: demographic, clinical, left ventricular morphologic and functional and angiographic, perioperative: type of operation, type and number of applied conduits, in-hospital morbidity and mortality, and post-operative: demographic, clinical, left ventricular morphologic and functional and angiographic characteristics. Mean postoperative follow-up period was 5.97 +/- 4.27 years. Results: Hypertension was found in 52.7% of patients before the operation, and it was the most frequent risk factor, without any differences between different age groups, but significantly more often in females (p = 0.0001), diabetics (p = 0.0001), and patients with preserved LV function (p = 0.011). Although significantly correlated with in-hospital morbidity (r = 0.085 and p = 0.023), HTA was not identified as independent predictor. The most predictable was the occurrence of early neurological complications. HTA was also found to be a predictor of long life prognosis in CABG patients, but not as independent prognostic factor. Significant reduction in incidence was found in post-CABG patients (30.1%), which is most likely a result of applied pharmacologic treatment. ACE-inhibitors, Ca-antagonists and B-blockers were applied in 39.44%, 30.1% and 33.6% of patients respectively, with significant positive correlations found for all of them as follows: r = 0.221, p = 0.0001, r = 0.316, p = 000.1 and r = 0.093, p = 0.031. Conclusion: Hypertension is the most powerful risk factor in CAD patients who undergo CABG surgery in our country, and a powerful prognostic factor of early and late clinical outcome. There is a trend toward decreasing the incidence of HTA in post-CABG patients, as a result of improved pharmacologic treatment after the operation (Tab. 5, Fig. 1, Ref. 13). Full Text (Free, PDF) www.bmj.sk.
Keywords: cardiovascular risk factors; arterial hypertension; coronary artery disease; myocardial revascularisation